What world price? - Nelissa Jamora; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2012)
There is no consensus on what defines a reference for the world rice price. A review on rice as a differentiated commodity shed two important insights. First, it confirms that few studies have considered segmentation of rice in their price analysis. Second, Thai 5% brokens has often been considered the world reference price for rice but no empirical exercise has been carried out to validate this. This study analyzes the extent of market integration in the international rice market by generating empirical evidence on the cointegration of different export prices. We start our analysis with the assumption that rice is not a homogeneous good. In this context, we establish clusters by rice quality and determine which export markets best represent the world rice price within and across clusters. The study uses 19 monthly average export rice price quotations from January 2000 to July 2012 extracted from the FAO Global Information and Early Warning System food price database and from the Thai Rice Exporters Association. We also include FAO Export Price indices for high and low quality indica to assess their performance with other export prices. Our study contributes to the limited discussion on rice as a heterogeneous commodity. We validate Thai 5% brokens as the benchmark price for rice by examining its bivariate relationships with other export prices. We employ Johansen maximum likelihood procedure to confirm the long-run equilibrium relations and cointegration of price series. Then, we extend the error correction model to a multivariate cointegration analysis by cluster. We test for the Law of One Price, long run exclusion, and weak exogeneity to assess the dynamics of price transmission and determine how prices are related with one another. We build on this information and our knowledge of the rice market system to answer the question – What is the world rice price? We find evidence that the rice market is highly segmented. This suggests that there is no single answer to our research question. While we find that Thai 5% brokens is cointegrated with many other export prices and contributes strongly in defining long run equilibrium relations, there are several international rice prices that could be used as benchmarks. The results imply that failure to find cointegrating relations from world to domestic rice markets can be a result of failure to effectively define the appropriate international reference price. In price transmission analysis, we find that it is imperative to examine the types of rice and to discuss the relevance of specific markets to the benchmark price based on understanding of rice trade structure. This study affirms the importance of having up-to-date and reliable sources of rice prices both in the export and domestic markets, accounting for differences in quality.
Keywords: C32; Q11; Q17; Q18; 330; rice; price transmission; cointegration; world price